The role of social media in managing supplier attractiveness: An investigation of business-to-business markets. Issue 5 (17th December 2019) - Tóth, Zsófia; Liu, Martin; Luo, Jun; Braziotis, Christos
Abstract : Purpose: Managing attractiveness is a constant challenge to mobilize relationship-specific investments, especially in a business environment increasingly enhanced by social media (SM) activities. There is limited knowledge on how SM activities contribute to supplier attractiveness, so decisions about strategizing with SM and consequent resource allocations become highly uncertain. The purpose of this paper is to examine how suppliers' SM activities influence supplier attractiveness. Design/methodology/approach: Altogether, 57 senior managers were interviewed: 32 semi-structured in-depth interviews were conducted with senior managers in strategic decision-making roles regarding SM on the supplier side, along with 20 senior managers responsible for purchasing or looking after supplier development; one-to-one interviews were complemented by a focus group with 5 senior managers on the buyer side. Findings: The study reveals an inverse U-shaped relationship between the intensity of the supplier's SM activity and its attractiveness and offers a set of propositions about the influence of SM on supplier attractiveness, with special regard to the perceived risks of increased transparency and becoming "too social" on SM. Practical implications: The study highlights SM management results for supplier attractiveness and their impact areas on business growth and supply chain development. Originality/value: This paper provides in-depth insights into the role of SM in managing supplier attractiveness. Various effects of SM activities are identified that aim to contribute to the body of literature on supplier attractiveness as well as SM management in buyer–supplier relationships.